Grammar in newspaper headlines - Prášková, Eva (Univerzita Pardubice, 2009)
This bachelor thesis deals with the grammar of newspaper headlines. Its aim is to establish the most frequently used grammatical features and structures that occur in headlines and which were analysed in a corpus. The corpus consists of 200 randomly chosen headlines collected from 6 different British newspapers and was created just for the purpose of this work.
Gramatika novinových titulků
Keywords: novinové nadpisy; Gramatika; block language; Britský tisk; newspaper headlines; Grammar; block language; British press